Natural Phenylethanoid Supplementation Alleviates Metabolic Syndrome in Female Mice Induced by High-Fructose Diet - Xiujun Zhan; Xiujun Zhan; Mingshuai He; Mingshuai He; Jierong Pei; Jierong Pei; Wenjing Fan; Wenjing Fan; Charity Ngina Mwangi; Peng Zhang; Peng Zhang; Xin Chai; et al. (Frontiers Media S.A., 2022)
Tyrosol (T), hydroxytyrosol (H), and salidroside (S) are typical phenylethanoids and also powerful dietary antioxidants. This study aimed at evaluating the influence of three natural phenylethanoids, which are dietary phenylethanoids of natural origins, on reversing gut dysbiosis and attenuating nonalcoholic fatty liver features of the liver induced by metabolic syndrome (MetS) mice. C57BL/6J female mice induced with high-fructose diet were established and administrated with salidroside, tyrosol, and hydroxytyrosol for 12 weeks, respectively. Biochemical analysis showed that S, T, and H significantly improved glucose metabolism and lipid metabolism, including reduced levels of total cholesterol insulin (INS), uric acid, low-density lipoprotein cholesterol (LDL-C), and aspartate aminotransferase (ALT). Histopathological observation of the liver confirmed the protective effects of S, T, and H against hepatic steatosis, which were demonstrated by the results of metabolomic analysis, such as the improvement in glycolysis, purine metabolism, bile acid, fatty acid metabolism, and choline metabolism. Additionally, 16S rRNA gene sequence data revealed that S, T, and H could enhance the diversity of gut microbiota. These findings suggested that S, T, and H probably suppress lipid accumulation and have hepatoprotective effects and improve intestinal microflora disorders to attenuate metabolic syndromes.